A STUDY ON ORGANIZATIONAL CITIZENSHIP AND JOB SATISFACTION IN INDIA'S HOTEL INDUSTRY - Kant, Shashi; Singh, Saumya; Singh Chauhan, Hitendra; Indora, Deepali; Kaintura, Sapna (The journal of contemporary issues in business and government, 2022)
In many regions of the India, finding and keeping skilled staff is a major issue in the hospitality business. As a result, job happiness is becoming increasingly crucial for the long-term development of the work force and its ramifications for regions and destinations. As a result, the goal of this research is to better understand the elements that influence job satisfaction.An online questionnaire was used to examine 116 employees on various areas of job satisfaction. According to data analysis, the most essential variables for job satisfaction are a positive relationship within the team, Shift timing and working hours, personal growth chances, fair pay and promotion policy. The findings point to crucial topics and directions for further job satisfaction research. For practitioners, the study provides useful information on how to promote employee job satisfaction in a long-term and effective manner.